A randomized, double-blind, placebo-controlled trial of intravenous alpha-1 antitrypsin for ARDS secondary to COVID-19 - Hennessy, Martina (My University, 2022)
Background: Patients with severe coronavirus disease 2019 (COVID-19) develop a febrile pro-inflammatory cytokinemia with accelerated progression to acute respiratory distress syndrome (ARDS). Here we report the results of a phase 2, multicenter, randomized, double-blind, placebo-controlled trial of intravenous (IV) plasma-purified alpha-1 antitrypsin (AAT) for moderate to severe ARDS secondary to COVID-19 (EudraCT 2020-001391-15). Methods: Patients (n = 36) were randomized to receive weekly placebo, weekly AAT (Prolastin, Grifols, S.A.; 120 mg/kg), or AAT once followed by weekly placebo. The primary endpoint was the change in plasma interleukin (IL)-6 concentration at 1 week. In addition to assessing safety and tolerability, changes in plasma levels of IL-1β, IL-8, IL-10, and soluble tumor necrosis factor receptor 1 (sTNFR1) and clinical outcomes were assessed as secondary endpoints. Findings: Treatment with IV AAT resulted in decreased inflammation and was safe and well tolerated. The study met its primary endpoint, with decreased circulating IL-6 concentrations at 1 week in the treatment group. This was in contrast to the placebo group, where IL-6 was increased. Similarly, plasma sTNFR1 was substantially decreased in the treatment group while remaining unchanged in patients receiving placebo. IV AAT did not definitively reduce levels of IL-1β, IL-8, and IL-10. No difference in mortality or ventilator-free days was observed between groups, although a trend toward decreased time on ventilator was observed in AAT-treated patients. Conclusions: In patients with COVID-19 and moderate to severe ARDS, treatment with IV AAT was safe, feasible, and biochemically efficacious. The data support progression to a phase 3 trial and prompt further investigation of AAT as an anti-inflammatory therapeutic. Funding: ECSA-2020-009; Elaine Galwey Research Bursary.
PUBLISHED
Keywords: Randomized control trial; Interleukin-6; Inflammation; Cytokines; COVID-19; Coronavirus; Acute respiratory distress syndrome; Alpha-1 antitrypsin; Clinical trial